Pengaruh Sistem Informasi Terhadap Kesadaran Masyarakat Wajib Pajak Pada Kantor Samsat Blang Bladeh - Rizky Maulana (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
This study aims to determine the effect of information systems on public awareness of paying taxpayers at the Blang Bladeh Samsat Office. This type of research is associative research. Data collection in this study was carried out through a survey approach with a quantitative descriptive type of research by distributing questionnaires to 100 respondents, while the population used in this study was the tax payers in the city of Blang Bladeh. Data collection techniques were carried out by interviews, questionnaires and documentation studies. The data analysis tool used in this study uses SPSS (Statistical Product Software Solution). The results of this study indicate that the information system has a positive and significant effect on public awareness of paying taxpayers at the SAMSAT blang bladeh office.